Abordaje terapéutico del aborto espontáneo incompleto en mujeres de un hospital de Lima, Perú - Alvarado-Franco, Samanta Dayana (2026)
Introduction: In Peru, an estimated 350,000 abortions occur annually, with complications representing the fourth leading direct cause of maternal mortality.The majority are incomplete spontaneous abortions, associated with factors such as diabetes, hypertension, and thyroid disease. Three management approaches exist: expectant management, medical management, and surgical management. No national consensus exists for the management of this condition. Objective: To describethe characteristics of management for incomplete spontaneous abortion in women aged 18–45 at Hospital III Suárez Angamos. Materials and Methods: A retrospective, observational, descriptive study was conducted using electronic medical records of women aged 18–45 diagnosed with incomplete spontaneous abortion between June1 and December 31, 2024. A total of 321 participants were included. Results: Most women were 18–34 years old (62.9%), 3.4% had complicated abortions, and 15.0% presented comorbidities. Medical management with misoprostol was most commonly used (53.9%), followed by surgical management (36.1%), which was more frequent in cases with endometrial thickness ≥30 mm and uterine size ≥12 cm. Some patients managed expectantly or with medical management required additional treatment, over 60% of which involved misoprostol. Conclusions: Medical management was thefirst-line approach for incomplete spontaneous abortion. However, limited evidence remains regarding clinical parameters, such as endometrial thickness, which are essential to guide treatment choice and confirm its success.